The role of GLP-1 receptor agonists during COVID-19 pandemia: a hypothetical molecular mechanism - Banerjee, Yajnavalka (2021)
Introduction: A number of anti-diabetic treatments have been favored during the continuing spread of the current SARS-CoV-2 pandemic. Glucagon-like peptide-1 receptor agonists (GLP1-RAs) are a group of antidiabetic drugs, the glucose-reducing effect of which is founded on augmenting glucose-dependent insulin secretion with concomitant reduction of glucagon secretion and delayed gastric emptying. Apart from their glucose-lowering effects, GLP1-RAs also exert a plethora of pleiotropic activities in the form of anti-inflammatory, anti-thrombotic, and anti-obesogenic properties, with beneficial cardiovascular and renal impact. All these make this class of drugs a preferred option for managing patients with type 2 diabetes (T2D), and potentially helpful in those with SARS-CoV2 infection. Areas covered: In the present article we propose a hypothetical molecular mechanism by which GLP1-RAs may interact with SARS-CoV-2 activity. Expert opinion: The beneficial properties of GLP1-RAs may be of specific importance during COVID-19 infection for the most fragile patients with chronic comorbid conditions such as T2D, and those at higher cardiovascular and renal disease risk. Yet, further studies are needed to confirm our hypothesis and preliminary findings available in the literature.